Halophilic archaea cultivated from surface sterilized middle-late eocene rock salt are polyploid. - Salla T Jaakkola (Public Library of Science (PLoS), 2014)
Live bacteria and archaea have been isolated from several rock salt deposits of up to hundreds of millions of years of age from all around the world. A key factor affecting their longevity is the ability to keep their genomic DNA intact, for which efficient repair mechanisms are needed. Polyploid microbes are known to have an increased resistance towards mutations and DNA damage, and it has been suggested that microbes from deeply buried rock salt would carry several copies of their genomes. Here, cultivable halophilic microbes were isolated from a surface sterilized middle-late Eocene (38-41 million years ago) rock salt sample, drilled from the depth of 800 m at Yunying salt mine, China. Eight unique isolates were obtained, which represented two haloarchaeal genera, Halobacterium and Halolamina. We used real-time PCR to show that our isolates are polyploid, with genome copy numbers of 11-14 genomes per cell in exponential growth phase. The ploidy level was slightly downregulated in stationary growth phase, but the cells still had an average genome copy number of 6-8. The polyploidy of halophilic archaea living in ancient rock salt might be a factor explaining how these organisms are able to overcome the challenge of prolonged survival during their entombment.